The vitality of very-large-scale motions upstream of an overflow structure - Zili Yan; Dejun Zhu; Danxun Li (AIP Advances, 2023)
The flows upstream of a run-of-river dam, commonly utilized as an overflow structure on rivers, are complex due to heterogeneities in both streamwise and spanwise directions. In particular, very-large-scale motions (VLSMs) are greatly influenced by the overflow structure, yet relevant understandings remain limited. Reported as novel coherent structures in turbulent flows, VLSMs are recognized with the scale up to several and tens of the outer-scaled unit, and they contribute significantly to turbulent transport and mixing. To fill the gap, experiments with particle image velocimetry were conducted to investigate the vitality of VLSMs upstream of a model dam. Measurements were designed to cover broad hydraulic scope with flow heterogeneities. The results reveal that VLSMs in the present flow scenario show noticeable characteristics in both streamwise and spanwise directions. Compared to those in uniform flows, the VLSMs in present flows are found to be more energetic and stress-active.